Effects of non‐euphoric plant cannabinoids on muscle quality and performance of dystrophic mdx mice. (9th September 2018) - Iannotti, Fabio Arturo; Pagano, Ester; Moriello, Aniello Schiano; Alvino, Filomena Grazia; Sorrentino, Nicolina Cristina; D'Orsi, Luca; Gazzerro, Elisabetta; Capasso, Raffaele; De Leonibus, Elvira; De Petrocellis, Luciano; Di Marzo, Vincenzo
Abstract : Background and Purpose: Duchenne muscular dystrophy (DMD), caused by dystrophin deficiency, results in chronic inflammation and irreversible skeletal muscle degeneration. Moreover, the associated impairment of autophagy greatly contributes to the aggravation of muscle damage. We explored the possibility of using non‐euphoric compounds present in Cannabis sativa, cannabidiol (CBD), cannabidivarin (CBDV) and tetrahydrocannabidivarin (THCV), to reduce inflammation, restore functional autophagy and positively enhance muscle function in vivo . Experimental Approach: Using quantitative PCR, western blots and [Ca 2+ ]i measurements, we explored the effects of CBD and CBDV on the differentiation of both murine and human skeletal muscle cells as well as their potential interaction with TRP channels. Male dystrophic mdx mice were injected i.p. with CBD or CBDV at different stages of the disease. After treatment, locomotor tests and biochemical analyses were used to evaluate their effects on inflammation and autophagy. Key Results: CBD and CBDV promoted the differentiation of murine C2C12 myoblast cells into myotubes by increasing [Ca 2+ ]i mostly via TRPV1 activation, an effect that undergoes rapid desensitization. In primary satellite cells and myoblasts isolated from healthy and/or DMD donors, not only CBD and CBDV but also THCV promoted myotube formation, in this case, mostly via TRPA1 activation. In mdx mice, CBD (60 mg·kg −1 ) and CBDV (60 mg·kg −1 ) prevented the loss of locomotor activity, reduced inflammation and restored autophagy. Conclusion and Implications: We provide new insights into plant cannabinoid interactions with TRP channels in skeletal muscle, highlighting a potential opportunity for novel co‐adjuvant therapies to prevent muscle degeneration in DMD patients. Linked Articles: This article is part of a themed section on 8 th European Workshop on Cannabinoid Research. To view the other articles in this section visithttp://onlinelibrary.wiley.com/doi/10.1111/bph.v176.10/issuetoc